2021
DOI: 10.3390/atmos12111488
|View full text |Cite
|
Sign up to set email alerts
|

Microphysical Characteristics and Environmental Isotope Effects of the Micro-Droplet Groups under the Action of Acoustic Waves

Abstract: Acoustics can cause particles/droplets to agglomerate in the air medium, thereby accelerating gravity sedimentation. To assess the microphysical characteristics and environmental isotope effects of micro-droplet groups under the action of acoustic waves, an air chamber experimental platform was established, and 100 groups of controlled experiments were conducted. The characteristic particle size, size spectrum, isotope values, corresponding linear relationships with hydrogen and oxygen, and d values were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Micron particles in acoustic fields can be evoked to vibrate at different amplitudes due to the combined effect of inertial force and viscous force (Zhou et al, 2017). Thus, the particles with different sizes in acoustic fields will have different vibration amplitudes, and agglomeration process due to acoustic stimulation occurs (Bai et al, 2021).…”
Section: Literature Review Of Acoustic Wave Impacts On Precipitationmentioning
confidence: 99%
See 2 more Smart Citations
“…Micron particles in acoustic fields can be evoked to vibrate at different amplitudes due to the combined effect of inertial force and viscous force (Zhou et al, 2017). Thus, the particles with different sizes in acoustic fields will have different vibration amplitudes, and agglomeration process due to acoustic stimulation occurs (Bai et al, 2021).…”
Section: Literature Review Of Acoustic Wave Impacts On Precipitationmentioning
confidence: 99%
“…Those limitations mainly are (1) knowledge shortage of physical mechanism of acoustic wave impact on precipitation stimulation, (2) manufacture of the devices for providing strong acoustic waves which can propagate to high sky with an altitude of several hundreds or even 1 to 2 kilometers, (3) a cloud and precipitation monitoring system for obtaining acoustic impacts on clouds and then precipitation, and (4) an effective method to evaluate the efficiency of acoustic wave impacts on stimulation of precipitation quantitatively. To overcome those limitations, in recent years, the feasibility of the technology has been explored through numerical modeling analysis (Markauskas et al, 2015;Shi et al, 2020) and indoor cloud chamber experiments (Bai et al, 2021). Meanwhile, the field experimental explorations of acoustic wave impacts on natural cloud of precipitation processes were widely conducted to evaluate the efficiency of precipitation enhancement (Shi et al, 2021;Wei et al, 2021).…”
Section: Literature Review Of Acoustic Wave Impacts On Precipitationmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2002, Hou et al (2002 performed an acoustic intervention experiment at relatively lower frequency of 20-50 Hz, and found that the acoustic frequency corresponding to the optimal agglomeration effect is 20 Hz. For 40-100 Hz acoustic intervention on microdroplets, Bai et al (2020); Bai et al (2021a); Bai et al (2021b) found that the particle size increment was significantly affected by the sound frequency, and the droplets isotope values increased after interference of acoustics. He et al (2021) conducted experiments on droplets by combined sound waves of 200-600 Hz and electric field.…”
Section: Introductionmentioning
confidence: 99%